Teks Prosedur dalam Peningkatan Kemampuan Menulis Bahasa Inggris Siswa Sekolah Dasar - Wakerkwa, Dian Agustina Purwanto (Lembaga Penelitian dan Pengabdian Masyarakat, 2023)
Having the ability to write in English has started to become a necessity as a form of active reaction to the development of global communication where English is the official means of international communicaation. It is a huge challenge for students, especially in Indonesia. Of the four language skills, writing has its own challenges and is still considered the most difficult skill to master by most Indonesian students. The quality of a writing is assessed by four indicators, development of ideas, vocabulary choices, and the proper use of grammar and punctuation. These four variables must then be presented in a writing structure appropriate to the genre. The present research is part of a community service activity where the research target is students at an elementary school in Merauke City. There are several stages in the activity, observation, teaching, and post-test. Preliminary observations showed students' weak writing skills which later became the main consideration in preparing teaching materials. The writing learning method using procedural text is selected on the basis of the suitability of students' interests and abilities. The results of the post-test found that more than half of the total number of students showed an increase in writing ability with procedure text and most errors are found in the use of grammar